Towards a socio cognitive perspective of presenteeism, leadership and the rise of robotic Interventions in the workplace - Lopes, Sara Lampreia (2022)
This thesis intends to investigate the relationship between the presenteeism phenomenon and the leadership construct, by analyzing a new concept in the literature, leadership presenteeism. Second, it explores robotic leadership and the impact of human-leadership styles in teams headed by social robots. Third, it investigates the role of robots as health-promoting agents within workplaces, contributing to workers’ improvements in a set of organizational variables. The thesis includes seven empirical studies, divided in four papers. Paper 1 findings suggest that individuals perceive themselves as less productive when they work with a leader with a psychological or contagious illness. Paper 2 reveals that robots can properly perform leadership roles while leading human teams, and achieve the same organizational outcomes as human leaders. Moreover, robots performing both transformational and transactional leadership styles can impact positively different organizational outcomes. In paper 3 a robot was used as a health behavior promoting agent in a single-arm intervention, with two assessment points in time. Results showed that the intervention with the robot enabled to improve a set of psychological health behavior constructs. Finally, paper 4 aimed to compare the health behavior change intervention between two groups: one guided by a robotic agent and the other by a human agent. Results showed that the intervention with the robot agent was associated with improvements in individuals’ productivity despite presenteeism and well-being levels. This thesis contributes to the understanding of the relationship between presenteeism and leadership constructs, while seeks also to contribute and extend SCT and HAPA theoretical framework.